1984
DOI: 10.1002/chin.198401228
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS AND PREGNANCY TERMINATING ACTIVITY OF 2‐ARYLIMIDAZO(2,1‐A)ISOQUINOLINES AND ISOINDOLES

Abstract: Die Phenacylbromide (I) reagieren mit dem 1‐Aminoisochinolin (II) in Gegenwart von Basen zu den Arylimidazoisochinolinen (III), die auch aus Isochinolin (V) und (I) über die Phenacylisochinoliniumbromide (IV) mit FeCl3/NH3 zugänglich sind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The crude reaction product obtained by Pd‐catalyzed intramolecular CDC of 1‐benzyl‐4‐phenyl‐1 H ‐imidazole ( 1l ) was purified by flash chromatography on silica gel with a mixture of DCM and MeOH (93:7) as eluent, followed by crystallization from CHCl 3 /hexane to give 2l as a pale beige solid (119 mg, 50 % yield): ): m.p. 190–192 °C (Lit[11f] 172–175 °C; Lit 152–153 °C). GLC analysis showed that 2l had chemical purity higher than 98 %.…”
Section: Methodsmentioning
confidence: 99%
“…The crude reaction product obtained by Pd‐catalyzed intramolecular CDC of 1‐benzyl‐4‐phenyl‐1 H ‐imidazole ( 1l ) was purified by flash chromatography on silica gel with a mixture of DCM and MeOH (93:7) as eluent, followed by crystallization from CHCl 3 /hexane to give 2l as a pale beige solid (119 mg, 50 % yield): ): m.p. 190–192 °C (Lit[11f] 172–175 °C; Lit 152–153 °C). GLC analysis showed that 2l had chemical purity higher than 98 %.…”
Section: Methodsmentioning
confidence: 99%
“…Imidazo[2,1‐ a ]isoquinolines are of interest due to their anti‐inflammatory potential , antirhinoviral , long‐acting local anesthetic properties , and as antiulcer agents . Hou et al used ionic liquid for the synthesis of imidazo[2,1‐ a ]isoquinolines 19 by stirring a mixture of α‐tosyloxyacetophenone 17 , 1‐aminoisoquinoline 18 , and Na 2 CO 3 in BPyBF 4 (Scheme ).…”
Section: Fused Heterocycles Containing Imidazole Ringmentioning
confidence: 99%
“…Isoindoles are promising active biological materials [1,2] with interesting spectral properties and are the subject of studies for important theoretical questions, such as: aromaticity, tautomerism [3][4][5][6][7] and represent an important source of reagents used in cycloaddition reactions, [8][9][10][11][12] the study of organic reaction mechanisms, new rearrangements [13,14].…”
Section: Introductionmentioning
confidence: 99%